1998
DOI: 10.3171/jns.1998.89.4.0659
|View full text |Cite
|
Sign up to set email alerts
|

Primary cervical melanoma with brain metastases

Abstract: Primary intramedullary melanoma is a very rare tumor that occurs most frequently in the middle or lower thoracic spinal cord. The authors present a case of primary cervical cord melanoma that developed in a 62-year-old man who was surgically treated and subsequently underwent radiation therapy. Clinical and histogenetic features of this neoplasm and results of chemo-. radio-, and immunotherapy are reported. Both "dysembryogenetic" and "mesodermal" hypotheses on the origin of primary spinal melanoma are discuss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 51 publications
0
23
0
Order By: Relevance
“…Salpietro et al ( 33 ) reported that specific immunotherapy was an important adjuvant method in the treatment of small residual malignant melanoma lesions, and presented low toxicity. High doses of IFNβ or IFNα-2b may improve disease control and prolong survival time, but the dosage required is disputed and difficult to tolerate.…”
Section: Discussionmentioning
confidence: 99%
“…Salpietro et al ( 33 ) reported that specific immunotherapy was an important adjuvant method in the treatment of small residual malignant melanoma lesions, and presented low toxicity. High doses of IFNβ or IFNα-2b may improve disease control and prolong survival time, but the dosage required is disputed and difficult to tolerate.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, melanocytes can be found in skin, mucous membranes, parenchyma, and uvea. [ 3 4 5 ] In most instances, melanomas involving the CNS represent metastatic disease. Melanoma is the most common tumor, after lung and breast cancers, which produces brain metastases.…”
Section: Discussionmentioning
confidence: 99%
“…[ 11 ] The differential diagnoses of leptomeningeal tumors include meningioma, meningeal melanocytoma, leptomeningeal melanosis, metastases, and sarcoma. [ 4 5 ] It is difficult to distinguish primary CNS melanoma from metastatic melanoma on neuroimages alone. [ 12 ] Hayward[ 13 ] proposed the following factors for establishing a diagnosis of a primary CNS melanoma: (a) No malignant melanoma outside the CNS, (b) leptomeningeal involvement, (c) intramedullary spinal lesions, (d) hydrocephalus, (e) tumor location in the pituitary or pineal gland, and (f) a single intracerebral lesion.…”
Section: Discussionmentioning
confidence: 99%
“…8) The average survival of patients with primary spinal malignant melanoma is 5–6 years after the onset of symptoms, which is clearly longer compared to central nervous system metastasis of cutaneous malignant melanoma, which exhibits a fast progression with systemic spread and leads to a fatal outcome in <6 months. 5,8),13) A previous report stated that the presence of the blood brain barrier in the spinal cord prevents hematogenous spread and hampers the process of metastasis. 4) Considering the slow progression primary spinal malignant melanoma, it is critical to establish a precise diagnosis, because patients should undergo tumor removal to slow down the onset of neurological deficits, even in the case of central nervous system dissemination.…”
Section: Discussionmentioning
confidence: 99%
“…4,8) The mean survival time of patients with primary spinal malignant melanoma is approximately 6 years after symptom onset. 5,8) These facts indicate that surgical excision and postoperative adjuvant therapy, such as radiotherapy and chemotherapy, should be used for slowing the onset of neurological deficits, even in cases with central nervous system dissemination. 3,9) To our knowledge, this is the first report of an incidental discovery of primary spinal malignant melanoma in a patient who was treated with only surgery and who survived >5 years without recurrence or dissemination.…”
Section: Introductionmentioning
confidence: 99%